Gemcitabine hydrochloride microspheres used for intravesical treatment of superficial bladder cancer: a comprehensive in vitro/ex vivo/in vivo evaluation - Karavana SY; Ay Şenyiğit Z; Çalışkan Ç; Sevin G; İlem Özdemir D; Erzurumlu Y; Şen S; Baloğlu E (Dove Medical Press, 2018)
Sinem Yaprak Karavana,1 Zeynep Ay Şenyiğit,2 Çağrı Çalışkan,3 Gülnur Sevin,4 Derya İlem Özdemir,2 Yalçın Erzurumlu,5 Sait Şen,6 Esra Baloğlu1 1Department of Pharmaceutical Technology, Faculty of Pharmacy, Ege University, Izmir, Turkey; 2Department of Pharmaceutical Technology, Faculty of Pharmacy, Izmir Katip Çelebi University, Izmir, Turkey; 3Department of Radiopharmacy, Faculty of Pharmacy, Ege University, Izmir, Turkey; 4Department of Pharmacology, Faculty of Pharmacy, Ege University, Izmir, Turkey; 5Department of Biochemistry, Faculty of Pharmacy, Ege University, Izmir, Turkey; 6Department of Pathology, Faculty of Medicine, Ege University, Izmir, Turkey Introduction: Bladder cancer is responsible for more than 130,000 deaths annually worldwide. Intravesical delivery of chemotherapeutic agents provides effective drug localization to the target area to reduce toxicity and increase efficacy. This study aimed to develop an intravesical delivery system of gemcitabine HCl (Gem-HCl) to provide a sustained-release profile, to prolong residence time, and to enhance its efficiency in the treatment of bladder cancer. Materials and methods: For this purpose, bioadhesive microspheres were successfully prepared with average particle size, encapsulation efficiency, and loading capacity of 98.4 μm, 82.657%±5.817%, and 12.501±0.881 mg, respectively. For intravesical administration, bioadhesive microspheres were dispersed in mucoadhesive chitosan or in situ poloxamer gels and characterized in terms of gelation temperature, viscosity, mechanical, syringeability, and bioadhesive and rheological properties. The cytotoxic effects of Gem-HCl solution, Gem-HCl microspheres, and Gem-HCl microsphere-loaded gel formulations were evaluated in two different bladder cancer cell lines: T24 (ATCC HTB4TM) and RT4 (ATCC HTB2TM). Results: According to cell-culture studies, Gem-HCl microsphere-loaded poloxamer gel was more cytotoxic than Gem-HCl microsphere-loaded chitosan gel. Antitumor efficacy of newly developed formulations were investigated by in vivo studies using bladder-tumor-induced rats. Conclusion: According to in vivo studies, Gem-HCl microsphere-loaded poloxamer gel was found to be an effective and promising alternative for current intravesical delivery-system therapies. Keywords: gemcitabine HCl, intravesical chemotherapy, superficial bladder cancer microspheres, mucoadhesive gel, in situ gel